Peningkatan Prestasi Belajar melalui Metode Mind Map dalam Pembelajaran PAI Siswa Kelas XI Tehnik Komputer Jaringan 2 SMKN I Kras Kediri - Mabruroh, Lu'luatul (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2014)
The study is intended to improve the students’ achievement of class XI TKJ 2 SMKN1 Kras by implementing mind mapping in PAI teaching. It was intentionallyselected since it could activate the left and the right brain simultaneously so thatstudents could achieve the PAI teaching objectives including knowing, doing andpracticing in daily life. This study used Classroom Action Research (CAR). Theresult of the study showed that the implementation of mind mapping method inIslamic education (PAI) learning in class XI TKJ 2 SMKN 1 Kras conducted intwo cycles could improve students’ achievement in both cognitive and affectivescores.